A COMPARATIVE STUDY BETWEEN TEACHING VOCABULARY USING TOTAL PHYSICAL RESPONSE AND DIRECT METHOD: THE CASE OF THE FOURTH GRADE STUDENTS OF SD N 04 KARANGBRAI BODEH PEMALANG - Ratna kusumawardhani; Hery Sulistyanto (ETERNAL (English Teaching Journal), 2013)
The objectives of the research are (1) to describe the mastery of English vocabulary of the fourth graders of SD N 04 Karangbrai in the academic 2010/2011 using Total Physical Response and Direct Method, (2) to identify the advantages and disadvantages of Total Physical Response and Direct Method in teaching foreign language vocabulary, (3) to describe whether there is or not any significant difference between the mastery of English vocabulary of the fourth graders of SD N 04 Karangbrai in the academic 2010/2011 using Total Physical Response and Direct Method.In this study, the writer used experimental research. The reason was the writer tried to compare two variables and observe their differences. The writer took two groups of the students for doing the research. In this research the writer used control and experimental group. The first group was taught by using direct method and the second group taught by Total Physical Response. The material of this research is vocabulary. The population of this research is the fourth graders of SD N 04 Karangbrai in the academic 2010/2011. The number population is 30 students.This research used test as an instrument. The writer uses oral and essay test, The oral test for Total Physical Response (TPR) and essay test for Direct Method (DM). The test is twenty items, in which each item are scored by one (1) point for right answer and zero (0) for wrong answers. After the data have been collected and analyzed,Based on t-result, the degree of freedom could be measured. The formula was used as follows = df = N1 + N2 – 2 so that the calculation is (30 + 30 – 2 ) = 58. The value of the table with df = of 5 % from the table is 1.672 it could be calculated that t- value is higher than t-table (10.477 > 1.672). It means that any significant difference between using Total Physical Response and Direct Method in teaching vocabulary. It can be seen from the average of experiment group ( x ) is 77.66 and control group ( y ) is 64.8. so the average of experimental group higher than of control group. The data prove the using Total Physical Response to teach vocabulary is effective.Key words: comparative, vocabulary, Total Physical Response, Direct Method, SD N 04 Karangbrai Bodeh Pemalang.